From anger to aggressive behaviour: a systematic analysis of the factors that influence the process - Luo, Jun (2016)
Service failure is an unfortunate reality in service encounters. Although much literature suggests that the consequences of service failure include low customer satisfaction and customer loyalty, and another stream of research concerns service recovery, research on customers’ aggressive behaviour as the consequence of service failure – a cause of severe problems for service organizations, customers and employees – remains under researched. To understand this important process and the factors that influence the process, the first objective for the current research is to understand the antecedents of customer aggressive behaviours. When a service fails, customers tend to engage in an appraisal process, as described in appraisal theory, to assess what caused the poor service. Specifically, the cognitive appraisal process can lead to some negative emotions, namely anger. The results of this research suggest that via attribution of blame, perceived injustice and severity evaluation, these appraisals elicit customer anger, and this anger increases the possibility of aggressive behaviour. Therefore, this thesis suggests that anger partially mediates the relationship between appraisals and aggressive behaviour. The second research objective concerns the appraisal process, specifically the role of consumer skepticism. Typical applications of cognitive appraisal theory have been limited to situations in which customers make causal inferences based on the information presented. However, the route of appraisal would be influenced when customers are skeptical towards company claims and information provided by companies. The research findings suggest that the relationship between customers’ appraisals (blame, perceived justice and severity evaluation) and anger level is stronger when customers are more skeptical about company claims. Hence, consumer skepticism acts as a moderator on the appraisal process and anger. The third research objective concerns the moderating factors influencing the relationship between anger and aggressive behaviour. Even if consumers have strong anger after appraising the service failure, not all consumers will engage in aggressive behaviours. Thus, current understanding of the key causal links between anger and aggressive behaviour is insufficient. This research assesses the eliciting factors influencing the anger—aggressive behaviour relationship, namely, group empowerment, loss of face, emotional contagion and consumer expertise. In order to fulfil the research objectives, this research adopts a mixed research method using a qualitative critical incident technique method (CIT) and a quantitative survey method. Through the adoption of CIT method in interviewing 30 participants, this research explores the triggers for customers’ aggressive behaviour. The interview results suggested two groups as triggers for customers’ aggressive behaviour. Group empowerment as a new measurement was developed in the interview stage. The research framework was then empirically tested with a sample of 399 respondents to examine the effects of these factors on customers’ aggressive behaviours. The survey results suggested that most of hypotheses were supported with an exception of educational level which was rejected, namely: (1) anger mediated the relationship between appraisal components and aggressive behaviour; (2) higher consumer skepticism strengthened the relationships of blame attribution—anger, perceived injustice—anger and service failure severity—anger; (3) the moderating effects of group empowerment, loss of face, emotional contagion and consumer expertise strengthened the anger—aggressive behaviour link; (4) educational level weakens while frequency strengthen the relationship between customer anger and aggressive behaviour; and (5) aggressiveness directly influences customers’ aggressive behaviour and unpleasant servicescape relates to customers’ aggressive behaviour. This thesis contributes to the service marketing literature on customers’ aggressive behaviours in threefold. First, this research used cognitive appraisal theory as a theoretical framework to examine customers’ aggressive behaviour, contributing to our understanding of the mediating factor for eliciting aggressive behaviour. Second, this research also contributes to the effect of skepticism on customers’ appraisal processes. Third, this research furthers our understanding of the factors leading from anger to aggressive behaviour by examining the moderating effects, namely, group empowerment, loss of face, emotional contagion and consumer expertise. Apart from the theoretical contribution, this research also yields a number of managerial implications for service operators. Primarily, this study assists service organizations in understanding how customers appraise service failure, and thus how responding to customer needs can alleviate customers’ anger and aggressive behaviours. Additionally, to further reduce customers’ anger and aggressive behaviours, service companies should inhibit the development of skepticism by adopting appropriate marketing communication strategies to enhance the credibility of their claims. Finally, service companies should enhance their service failure management skills.